Toward a geography of borderlands in the global age: borders and spaces of 'informal' activity - (:unkn) unknown (My University, 2012)
This work draws upon 20 years of research on border zones, peripheral areas, and the margins of State territory. Through a variety of fieldwork sites and case studies from central Africa to Morocco and Lebanon, I examine the multiple transformations of borders in a neoliberal era and question the place of territorial margins in a global world. Methodologically, the book develops a multiple-focus approach that is predominantly based on personal investigations and accordingly, makes ample room for the researcher's subjectivity. My research is primarily concerned with transgressive social practices in border zones and how the latter become instrumentalized by ordinary people. This play with the distortions created by the borders highlights the persistence of a State framework inherited from colonialism. Although some borderlands feature highly profitable activities from which they benefit, most borderlands appear as regions of tensions where identities are being rewrought, contested, asserted, and reinforced. In other words, border areas raise significant issues related to globalization. Most importantly, they show very clearly the discontinuities and inequalities that result from globalization processes. Empirical field observations demonstrated a strong link between border locations and informal activities, suggesting a key issue to reflect further on the geographies of informality and illegality. The umbrella-concept of 'informal' seems to be increasingly popular in the social sciences. The concept could be defined as a transgressive playing with the rules. It needs to be tackled in a global spatial perspective and linked to a reflection about law. The nature of the link between borderland and informality has become a main issue to explore.
Keywords: African Research